Development of hepatitis C virus genotype 3a cell culture system. Issue 6 (14th July 2014) - Kim, Sulyi; Date, Tomoko; Yokokawa, Hiroshi; Kono, Tamaki; Aizaki, Hideki; Maurel, Patrick; Gondeau, Claire; Wakita, Takaji
<x xml:space="preserve">Abstract</x> Hepatitis C virus (HCV) genotype 3a infection poses a serious health problem worldwide. A significant association has been reported between HCV genotype 3a infections and hepatic steatosis. Nevertheless, virological characterization of genotype 3a HCV is delayed due to the lack of appropriate virus cell culture systems. In the present study, we established the first infectious genotype 3a HCV system by introducing adaptive mutations into the S310 strain. HCV core proteins had different locations in JFH‐1 and S310 virus‐infected cells. Furthermore, the lipid content in S310 virus‐infected cells was higher than Huh7.5.1 cells and JFH‐1 virus‐infected cells as determined by the lipid droplet staining area. Conclusion: This genotype 3a infectious cell culture system may be a useful experimental model for studying genotype 3a viral life cycles, molecular mechanisms of pathogenesis, and genotype 3a‐specific antiviral drug development. (Hepatology 2014;60:1837–1849)